Pengembangan Dan Inovasi Kurikulum Di MA At-Taufiq Grogol Diwek Jombang - Solechan Solechan; Siti Ma’rifah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2023)
There are two objectives of this study. The first is to describe the types and models of curriculum development at MA At-Taufiq Grogol, Diwek, Jombang. The second describes the kind of curriculum innovation at MA At-Taufiq Grogol Diwek Jombang. The results of the study indicate that the type of curriculum implemented at MA At-Taufiq is a Separated Curriculum, which is a form of curriculum organization that presents subjects separately with certain classifications. The curriculum development model used in MA At-Taufiq is carried out using the method of scientific learning in accordance with the demands of the applied curriculum, namely the K-13 and K.MA curricula with an implementation level of 70% of 100%, and the learning model is returned to the teachers of each subject. MA At-Taufiq develops innovations in the form of learning the yellow book and Qiroátul Qurán which are included in the local content curriculum as subjects. Aside from being local content subjects, learning the yellow book and Qiroátul Qurán is one of the foundation's programs and a hallmark of MA At-Taufiq. The innovation implemented at MA At-Taufiq was developed to address the issue of relevance by adding local content subjects to the curriculum, aiming to create graduates with the characteristics of a madrasa who can study books and teach them as well as the application of the STEM system to certain subjects that have similarities to KI/KD.